Biotic and environmental factors affect Southwest Atlantic saltmarsh use by juvenile fishes - Valiñas, Macarena Soledad (2012)
Fish habitat use is affected by biotic and environmental factors. These factors do not act in isolation; they commonly operate together, and can be modified by the presence of habitat structure, like vegetation. We studied at the Bahia Blanca estuary (38° 52' S, 62 0°6' W), the seasonal patterns of fish habitat use in a Spartina alterniflora saltmarsh and a contiguous tidal flat, and related them with biotic and environmental factors. The results showed that all fish species contributed to differences in the structure of fish assemblages between areas. The silverside Odontesthes argentinensis and the menhaden Brevoortia aurea were more abundant and smaller in size in the saltmarsh. In this area, the structure of fish assemblage was positively correlated with the structure of benthic community. The latter, was probably related to the high abundance of the polychaete Laeonereis acuta, the main benthic prey for fishes. Environmental factors that correlated with the structure of fish assemblages were particulate organic matter and sediment penetrability, both in the saltmarsh and in the tidal flat. This evidenced that in terms of physical and chemical factors studied, both areas present similar characteristics for fishes. This work highlights that saltmarshes in southern hemisphere provide both protection and food resources for fishes, and give support to the notion of saltmarshes as important fish habitat worldwide. © 2011 Elsevier B.V.